Parental decision making regarding consent to randomization on Children's Oncology Group AALL0932. Issue 4 (26th January 2021) - Parker, Kellee; Cottrell, Erika; Stork, Linda; Lindemulder, Susan
Abstract: Background: Within pediatric oncology, parental decision making regarding participation in clinical trials that aim to reduce therapy to mitigate side effects is not well studied. The recently completed Children's Oncology Group trial for standard‐risk acute lymphoblastic leukemia (AALL0932) included a reduction in maintenance therapy, and required consent for randomization immediately prior to starting maintenance. At our institution, 40% of children enrolled on AALL0932 were withdrawn from protocol therapy prior to randomization due to parental choice. This study sought to identify factors that impacted parental decision making regarding randomization on AALL0932. Procedure: Parents of children enrolled on AALL0932 at our institution were eligible if their child met criteria for the average‐risk randomization. Parents were invited to participate in a 30‐50‐minute phone interview. Questions focused on factors that shaped parental decision making about randomization, as well as their perspectives about the clinical trial experience more generally. Results: Fear of receiving less therapy and subsequent relapse was the predominant reason to decline randomization. Reasons given for consenting to randomization included trust in the physician, altruism, hope for less therapy, and potential for fewer side effects. Parents also reflected on ways to support future families making decisions about clinical trial participation. Conclusion: While many parents recognize the importance of clinical trials aiming to mitigate side effects, the fear of their own child relapsing with less than standard therapy may dissuade them from study participation. Recognizing and addressing these concerns will be important for enrollment and retention in future clinical trials.